2013
DOI: 10.3402/ljm.v8i0.21553
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific assessment of reduced coronary sinus flow in non-hypertensive patients with coronary artery disease at rest

Abstract: BackgroundAccess to data on the coronary flow in the coronary sinus (CS) can aid in the diagnosis of coronary artery disease (CAD). We tested the hypothesis that assessing the CS flow by transthoracic Doppler echocardiography (TTE) at rest can detect coronary artery stenosis in non-hypertensive patients.MethodsThe antegrade phase of coronary flow in the CS was analyzed and compared in 140 male and 135 female non-hypertensive subjects who had all undergone coronary angiography.ResultsThere were statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…They are all in vivo studies using transesophageal and transthoracic Doppler echocardiography [10][11][12][13][14]17,18], and none of these studies provided the precise correlation between the coronary sinus flow and the coronary infusion. Compared with in vivo studies, our study had some possible advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are all in vivo studies using transesophageal and transthoracic Doppler echocardiography [10][11][12][13][14]17,18], and none of these studies provided the precise correlation between the coronary sinus flow and the coronary infusion. Compared with in vivo studies, our study had some possible advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the coronary flow reserve in the coronary sinus has been used to diagnose severe coronary artery stenosis by transesophageal Doppler echocardiography due to inadequate visualization of the coronary arteries [10][11][12]. Recently, our studies showed that coronary sinus flow depicted by transthoracic Doppler echocardiography at rest can detect coronary artery stenosis in non-hypertensive [13], hypertensive [14], and diabetic hypertensive patients. These studies including transesophageal and transthoracic Doppler echocardiography still just depicted the coronary sinus flow (reserve) in the case of angiographically proven normal or stenotic coronary artery, but the exact relationship between coronary perfusion and coronary sinus flow remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] First, the parasternal right ventricular inflow tract view was obtained. The transducer was manipulated to visualize the mouth of the coronary sinus.…”
Section: Echocardiographic Measurementsmentioning
confidence: 99%
“…The velocity time integral was determined from digitized Doppler spectral envelopes. Third, the coronary sinus flow per minute (flow) was calculated according to the following formula [6][7][8][9][10][11] : Flow (mL/min) = π × D 2 /4 × velocity time integral × heart rate, where π is the ratio of the circumference of a circle to its diameter, and D is the diameter of the coronary sinus ( Figure 1). The average value of 3 spectral and planimetric envelopes was used.…”
Section: Echocardiographic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation